2016
DOI: 10.1038/srep21253
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional spherical spatial boundary conditions differentially regulate osteogenic differentiation of mesenchymal stromal cells

Abstract: The spatial boundary condition (SBC) arising from the surrounding microenvironment imposes specific geometry and spatial constraints that affect organogenesis and tissue homeostasis. Mesenchymal stromal cells (MSCs) sensitively respond to alterations of mechanical cues generated from the SBC. However, mechanical cues provided by a three-dimensional (3D) environment are deprived in a reductionist 2D culture system. This study investigates how SBC affects osteogenic differentiation of MSCs using 3D scaffolds wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 58 publications
(71 reference statements)
1
31
0
Order By: Relevance
“…The addition of biomimetic architecture most likely contributes through altered cytoskeletal reorganization that activates signaling pathways which increase osteoblast response. Previous studies have shown that cytoskeletal reorganization in response to implant surface or cell spanning of pores results in increased production of osteoblast markers (Lai et al, ; Li et al, ; Lo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of biomimetic architecture most likely contributes through altered cytoskeletal reorganization that activates signaling pathways which increase osteoblast response. Previous studies have shown that cytoskeletal reorganization in response to implant surface or cell spanning of pores results in increased production of osteoblast markers (Lai et al, ; Li et al, ; Lo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the mechanical properties of the cell's microenvironment, such as the substrate stiffness, have a fundamental effect on hMSC cell fate and function and impact tissue regeneration 6, 7, 8, 9. Recently, evidence is rising that the geometrical properties of the cell's environment also play an important role as regulators of cell behavior 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. Using geometric features, such as pore geometry, as a cue to direct tissue regeneration is compelling since it may allow a biomaterial to steer cell function purely by its shape and hereby contribute to tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are first indications that also single cell behavior is influenced by 3D surface curvature as cells were observed to actively migrate out of concave pits, while cells attached and proliferated on convex structures 11. Recently, it was shown that the diameter of 3D spherical pores in scaffold structures has an impact on cell morphology and osteogenic differentiation of MSCs 15. Together, these studies give the first evidence that cell behavior and organization are altered by curvatures much larger than the cell size.…”
Section: Introductionmentioning
confidence: 99%
“…Cell migration was clearly affected by the presence of the wells on the membrane; the presence of the geometrical cues led cells to migrate and start to adhere in the borders of the wells and proliferate to the centre direction. A recent study [72] shown that the diameter of 3D spherical pores could has influence on cellular morphological changes and osteogenic differentiation, even when curvatures are much larger than cell size. Herein, we developed concave spherical structures with a diameter of 500 µm (principle curvature (κ) = 1/250 µm −1 ), much larger than the size of SaOs-2 cell in a spread shape.…”
Section: Discussionmentioning
confidence: 99%